Effectiveness of Multimodal Intervention on Health-Related Quality of Life And Treatment Adherence among Hypertensive Patients in Selected Community Of Jumla, Nepal - Anika Dahal; Kamal Prasad Acharya (Nepal Journal of Public Health, 2026)
Background: Hypertension continues to be a global health issue, with rates of prevalence rising quickly in both developed and developing nations. Adherence to or compliance with hypertensive medications has significant economic and therapeutic consequences because nonadherence patients are at greater risk of developing complications affecting their health status and overall quality of life. The research aimed to determine the effects of multimodal intervention on health related quality of life and treatment adherence in hypertensive patients Methods: A quasi-experimental one-group pretest–posttest design was used among 218 hypertensive patients in Chandannath Municipality, Jumla. Participants aged ≥18 years, diagnosed with hypertension for at least 6 months, and on antihypertensive medication were included using non-probability consecutive sampling. Data were collected using WHOQOL-BREF and Hill-Bone Compliance Scale. A multimodal intervention package (education, counseling, leaflet, and telephonic follow-up) was implemented. Data were analyzed using SPSS version 21. Descriptive statistics and paired t-test were used. Results: The study revealed that 17.9% of respondents had perfect adherence during pretest which was significantly increased to 40.8% during posttest. Similarly, 16.1% of respondents had high health related quality of life during pre test which was significantly increased to 23.9% during posttest. Conclusions: It was concluded that the adherence and quality of life both were improved after the implementation of multimodal interventions. Therefore, the combination of educational interventions, attentive listening, and dialogue established within health facilities and community spaces can help patients make decisions about using strategies or actions to improve their treatment adherence and quality of life.